Bioactive peptide production and determination of functional properties using crude water extracts of Ulva lactuca (Chlorophyta) and Sargassum crassifolium (Phaeophyceae) collected from Sri Lanka. Issue 1 (31st December 2022) - Hamit, C.S.; Nam, K.C.; Abeyrathne, E.D.N.S.
ABSTRACT: Bioactive peptides of marine macroalgae consist of various functional properties. Ulva lactuca and Sargassum crassifolium are economically important, abundant green and brown macroalgae species in Sri Lanka that are rich in bioactive and functional components. However, few studies have been conducted to identify these bioactive and functional components of seaweeds in the local context. The aim of this study was to determine the best method to generate bioactive peptides from crude water extracts of Ulva lactuca and S. crassifolium and determine the functional properties of their hydrolyzates. Crude proteins of U. lactuca (sample: deionized water, 1:4) and S. crassifolium (sample: deionized water, 1:3) were extracted with water, using previously developed method and then subjected to protein hydrolysis by using papain (65°C, pH 6.00–7.00), α-chymotrypsin (37°C, pH 7.00–8.00), elastase (25°C, pH 8.0–8.50), and protease (60°C, pH 6.50–8.50) enzymes (1:100) under their optimum pH and temperatures for 0, 3, 6, 9, 12, 24 hours followed by heat inactivation at 100 ° C for 15 min. The best enzyme treatment was selected by conducting 15% SDS PAGE. Accordingly, proteins treated with enzymes followed by heat inactivation at 100°C for 15 min were selected as the best after considering the SDS-PAGE images. These hydrolyzates were used to determine the antioxidant activity (DPPH scavenging activity assay) and metal chelating activity (ferrozine method). Apart from peptides generated by elastase, all protein hydrolyzates had strong antioxidant activity (p < 0.05), but hydrolyzates produced from both crude extracts using α-chymotrypsin exhibited low Fe 2+ chelating activity (p < 0.05) while some showed metal releasing activity. Therefore, protein hydrolyzates produced from U. lactuca using papain, protease, and α-chymotrypsin, followed with heat inactivation showed strong antioxidant activity while having very low Fe 2+ chelating activity than all protein hydrolyzates of S. crassifolium . Highlights: Ulva lactuca and Sargassum crassifolium are promising marine algal resources found in Sri Lankan waters to produce bioactive peptides. Enzymatic hydrolysis can be carried out with different enzymes as papain, α-chymotrypsin, protease, and elastase enzymes under their optimum temperature and pH conditions to produce bioactive peptides. The crude peptides showed high DPPH radical scavenging activities but low Fe2+ chelating activity.